What Did Natural History have to do with Salvation? José de Acosta Sj (1540–1600) in the Americas - Ditchfield, Simon (Studies in church history, 2010)
At the southern foot of the Palatine Hill in Rome, a little more than one hundred metres due west of the triumphal arch erected by the emperor who is associated more than any other with the Christian conversion of the Old World — Constantine the Great - there stands another arch. Relocated from its original position at the eastern foot of the Palatine, more or less directly across from the biggest remaining ruin in the forum — that of the Basilica of Maxentius — it formed the monumental entrance to one of the most important botanic gardens in sixteenth-century Europe — the Orti farnesiani, which were given their definitive shape between 1565 and 1590. I propose that this second arch has reason to be considered as occupying a similar symbolic significance for the conversion of the New World.